A new candidate pulsating ULX in NGC 7793. Issue 4 (22nd March 2021) - Quintin, E; Webb, N A; Gúrpide, A; Bachetti, M; Fürst, F
ABSTRACT: We report here the discovery of NGC 7793 ULX-4, a new transient ultraluminous X-ray source (ULX) in NGC 7793, a spiral galaxy already well known for harbouring several ULXs. This new source underwent an outburst in 2012, when it was detected by XMM–Newton and the Swift X-ray telescope. The outburst reached a peak luminosity of 3.4 × 10 39 erg s −1 and lasted for about eight months, after which the source went below a luminosity of 10 37 erg s −1 ; previous Chandra observations constrain the low-state luminosity below ∼2 × 10 36 erg s −1, implying a variability of at least a factor 1000. We propose four possible optical counterparts, found in archival HST observations of the galaxy. A pulsation in the XMM–Newton signal was found at 2.52 Hz, with a significance of 3.4 σ, and an associated spin-up of f = 3.5× 10^-8 Hz s −1 . NGC 7793 is therefore the first galaxy to host more than one pulsating ULX.